Pengaruh Stimulasi Visual Untuk Meningkatkan Kemampuan Membaca Pada Anak Disleksia - Fajar Kawuryan; Trubus Raharjo (Universitas Muria Kudus, 2012)
This study aimed to investigate the influence of visual stimulation on the ability of dyslexic children to read in elementary school. The research was conducted in SD 2 and SD 3 rotten Holy Bae District. The sample inthis study were students in the category of children as dyslexic children (reading disorder). The sample in this study amounted to 21 students. This research uses experimental research by providing treatment to students through visual stimulation using a one group pre test-post test design. Data processing results show t1.2 different coefficient of 3.141 with a p = 0.005 (p smaller than 0.05). It is also indicated by the mean difference in both the average post-test data reading skills of elementary students are dyslexic 170.910 retata higher than pre test data reading skills of elementary school students are dyslexic of 90.173. These results indicate that there is a significant difference between pre test and post test of students' reading ability of dyslexic SD before and after treatment with visual stimulation. Based on the results of data analysis showed no differences in reading ability before and after visual stimulation treatment in children with dyslexia, in which the reading skills of elementary school students that dyslexia is given higher after treatment than before treatment is given.